The Effect of Community Based Intervention on People with Type 2 Diabetes Mellitus: Systematic Review - M Agung Akbar; Junaiti Sahar; Etty Rekawati; Ratu Ayu Dewi Sartika; Prateek Gupta (Public Health of Indonesia)
Background:The rising prevalence of Type 2 Diabetes Mellitus (T2D) has become a significant global health burden, with profound implications for healthcare systems and affected individuals. Strengthening primary healthcare services by integrating health and community-based interventions is critical for improving health outcomes. This rapid systematic review aimed to evaluate the effectiveness of community-based interventions in enhancing health outcomes for patients with T2D.